Matching Treatment and Offender: North Carolina, 1980-1982 - Marsden, Mary Ellen ([Verlag nicht ermittelbar], 1986)
These data were gathered in order to evaluate the implications of rational choice theory for offender rehabilitation. The hypothesis of the research was that income-enhancing prison rehabilitation programs are most effective for the economically motivated offender. The offender was characterized by demographic and socio-economic characteristics, criminal history and behavior, and work activities during incarceration. Information was also collected on type of release and post-release recidivistic and labor market measures. Recividism was measured by arrests, convictions, and reincarcerations, length of time until first arrest after release, and seriousness of offense leading to reincarceration.